Vacuum brazing method for connecting TZM alloy and graphite

By using Zr-3 active solder during vacuum brazing, the problem of low interface strength between TZM alloy and graphite in the prior art is solved, and the effect of combining high-strength interfaces and suitable for mass production is achieved.

CN120002114APending Publication Date: 2025-05-16ANHUI SHANGXINJINGGONG NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510231866.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-05-16

AI Technical Summary

Technical Problem

The prior art has problems such as low interface strength, coarse grains of the base material, and being unfavorable for mass production when welding TZM alloys and graphites.

Method used

Zr-3 active solder is used for vacuum brazing. By precision processing and cleaning of TZM alloy and graphite, the welding surface is ensured to be free of cracks or defects such as non-welding, and brazing is carried out under a high-temperature vacuum environment.

Benefits of technology

It realizes the high-strength interface combination of TZM alloy and graphite, and the interface shear strength reaches more than 19MPa, meeting the usage needs in high-temperature environments and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a vacuum brazing method for connecting a TZM alloy and graphite, and a TZM alloy / graphite welding part prepared by the vacuum brazing method for connecting the TZM alloy and the graphite. The method comprises the following steps: 1) processing, cleaning and drying a TZM alloy plate; (2) the graphite welding face is made to be in a tooth shape, and cleaning and drying are conducted; (3) the Zr-3 foil is cut to serve as welding flux, polishing treatment is carried out, and then cleaning and drying are carried out; (4) the TZM alloy plate, the Zr-3 foil and the graphite are sequentially stacked, and interfaces are in good physical contact; and 5) putting the assembled TZM / Zr-3 / graphite assembly into a vacuum furnace, vacuumizing, starting heating, carrying out vacuum brazing, carrying out gradient cooling or furnace cooling to room temperature, opening the furnace, and taking out the TZM / Zr-3 / graphite weldment. After the weldment is subjected to high-temperature treatment, a joint does not have remelting and tissue change, and the interface shear strength is almost unchanged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature vacuum brazing of heterogeneous materials, and in particular to a vacuum brazing method for connecting a TZM alloy and graphite using a Zr-3 active solder, and a TZM alloy / graphite welded part obtained by the method. Background Art

[0002] TZM alloy (Ti 0.4~0.55 wt%, Zr 0.06~0.12 wt%, C 0.01~0.04 wt%, the balance is Mo) has a melting point of up to 2600℃. By adding trace elements, Mo-Ti solid solution strengthening phase and dispersed titanium carbide and zirconium carbide strengthening phase can be formed, thereby increasing the recrystallization temperature and improving the high temperature performance of the alloy. Due to its high melting point, high strength, stable high temperature performance, and small thermal expansion coefficient (5.3*10 -6 K -1 ), low vapor pressure and strong corrosion resistance, it is widely used in medical, nuclear energy and aerospace fields. However, due to its high density (10.22g / cm 3 ), which limits its application to a certain extent. Graphite has a high melting point (3580±50℃) and a low density (1.7-1.9g / cm 3 ), high heat capacity, excellent heat dissipation performance, stable chemical properties, small thermal expansion coefficient (5.4*10 -6 K -1 ) and high thermal stress resistance, etc., and are widely used in the fields of medical, nuclear energy, and military. Welding TZM alloy and graphite to form a composite material can not only improve the thermal bearing capacity of the component, but also reduce the weight of the component, which is particularly suitable for X-ray tube rotating anode targets.

[0003] At present, the welding of TZM alloy and graphite mainly includes brazing, diffusion welding, SPS pressureless brazing, etc. Diffusion welding has high requirements on the surface quality of the parent material, and needs to be diffused for a long time under high temperature and certain pressure, which is easy to cause the coarsening of the parent material grains and reduce the performance of the parent material. CN105397264A discloses a vacuum hot pressing diffusion welding method of molybdenum and graphite, wherein the welding temperature is greater than 1700°C, the holding time is greater than 1h, which is easy to cause the recrystallization growth of the TZM alloy, and is not conducive to mass production and preparation. CN113770467A discloses a SPS pressureless brazing method of TZM alloy and graphite, which uses Ti as solder, the welding temperature is 1400-1630°C, the holding time is short, the effect on the parent material is small, the interface strength is high, but the equipment is expensive, and large-scale mass welding cannot be achieved, and it is difficult to meet the needs of mass production. CN114932283A discloses a eutectic reaction brazing process of graphite and TZM alloy, using Zr foil and V foil to perform gas pressure welding of TZM alloy and graphite, with a welding temperature of 1270-1350°C. Since Zr-V forms a eutectic reaction with a low melting point (1265°C), and the use temperature of the anode target of the X-ray tube is even close to 1450°C or above, it cannot meet the actual use requirements. Xiong Guogang et al. studied the welding performance of Zr brazing, but its interface strength was lower than 11MPa, which failed to meet the actual performance requirements (Research on Graphite and Molybdenum Alloy Brazing Materials and Brazing Process, Sichuan University, Master's Thesis, 2004). CN114453693A discloses a contact reaction of connecting TZM alloy and graphite with a pure zirconium layer, using pure zirconium for argon atmosphere brazing of TZM alloy and graphite, with a welding temperature of 1550-1650°C and a maximum strength of 19MPa, but the gas is introduced during the welding process, which is not conducive to the release of gas from the parent material and is not conducive to batch production. High-temperature vacuum brazing is in a certain vacuum state during the entire welding process, which is conducive to the release of gas from the parent material and is suitable for batch production. The obtained TZM / graphite interface joint has a high welding rate and the interface strength meets the actual use requirements. Summary of the invention

[0004] Technical issues In view of the problems existing in the prior art, the present invention aims to provide a vacuum brazing method for connecting TZM alloy and graphite and a welded part of TZM alloy and graphite obtained by the method. The vacuum brazing method for connecting TZM alloy and graphite according to the present invention can ensure that the TZM welded part forms a good metallurgical bond with the solder, and there are no defects such as cracks or unwelded interfaces.

[0005] Technical Solution According to a first aspect of the present invention, there is provided a vacuum brazing method for connecting a TZM alloy and graphite, comprising the following steps: Step 1: Turn or grind the TZM sheet, and clean and dry it; Step 2: Turn the graphite welding surface to form a toothed welding interface, and then clean and dry it; Step 3: Cut the Zr-3 foil as solder, grind it, clean it with acid, and dry it for later use; Step 4: stacking the TZM alloy plate obtained in step 1, the Zr-3 foil obtained in step 3, and the graphite obtained in step 2 in sequence to ensure good physical contact between the interfaces; Step 5: Place the assembled TZM / Zr-3 / graphite assembly into a vacuum furnace, then start heating after evacuating the vacuum furnace, with a heating rate of 15°C / min to 1200°C, and then heat to 1550~1630°C at 8°C / min, preferably 1570~1630°C, and keep it for 5~20 minutes for vacuum brazing, then gradually cool down or cool to room temperature with the furnace, open the furnace and take out the TZM / Zr-3 / graphite welded parts.

[0006] Preferably, the surface roughness Ra of the TZM plate obtained in step 1 is less than 0.8.

[0007] Preferably, the diameter of the TZM plate obtained in step 1 is 100-220 mm.

[0008] The surface of the TZM plate obtained in step 1 has no obvious vehicle marks, scratches or black spots, etc., and presents a uniform and good metallic luster.

[0009] Preferably, the cleaning in step 1 is performed by ultrasonic cleaning with dilute hydrochloric acid having a mass fraction of 3% to 15% for 10 minutes, then ultrasonic cleaning with deionized water for 10 minutes, and then cleaning and dehydration with alcohol.

[0010] Preferably, the toothed interface to be welded described in step 2 refers to an annular "V"-shaped groove formed on the interface to be welded.

[0011] Preferably, the graphite obtained in step 2 has a diameter of 100 to 220 mm.

[0012] Preferably, the depth of the annular "V"-shaped groove is 0.2-0.8 mm, and the width of the top of the groove is 0.3-1.0 mm.

[0013] Zr-3 is a zirconium alloy material, whose components include Zr+Hf≥99.2wt%, Hf≤4.5wt%, Fe+Cr≤0.2wt%, C≤0.05 wt%, N≤0.025 wt%, H≤0.005 wt%, and O≤0.16wt%.

[0014] Preferably, the thickness of the Zr-3 solder obtained in step 3) is 0.1-0.8 mm, preferably 0.2-0.4 mm.

[0015] Preferably, the diameter of the Zr-3 solder obtained in step 3 is 100-220 mm.

[0016] Preferably, the cross-section of the TZM plate obtained in step 1, the cross-section of the graphite obtained in step 2, and the Zr-3 solder obtained in step 3 are all the same in shape.

[0017] Preferably, the wire cutting and grinding process in step 3 refers to cutting the solder into corresponding shapes and then grinding with 400-mesh and 2000-mesh sandpaper to remove the surface oxide layer.

[0018] Preferably, the pickling in step 3 refers to mixing concentrated hydrochloric acid and deionized water in a weight ratio of 1:5-10, then immersing Zr-3 in the acid solution to clean surface impurities, then using deionized water ultrasonic cleaning to remove the acid solution, and finally drying for standby use.

[0019] The stacking in sequence described in step 4 means first placing the TZM alloy into a fixed tool, then placing the cleaned and dried Zr-3 sheet on the TZM welding surface, and then stacking the dried graphite on the Zr-3 sheet. The tooling is mainly used to keep the weldment centered and achieve good physical contact between the welding surfaces.

[0020] Preferably, the vacuum when starting the heating in step 5 is 7*10 -4 Up to 9*10 -4 Pa.

[0021] Preferably, the gradient cooling in step 5 refers to cooling to 1000° C. at a cooling rate of 10° C. / min after the brazing is completed, and then cooling to room temperature along with the furnace.

[0022] According to a second aspect of the present invention, there is provided a TZM alloy / graphite welded part prepared by the vacuum brazing method for connecting a TZM alloy and graphite according to the present invention.

[0023] Preferably, the interface joint shear strength of the TZM alloy / graphite welded part is preferably above 18 MPa, more preferably above 19 MPa, and even more preferably above 22 MPa.

[0024] Beneficial Effects The beneficial effects of the present invention are: 1. The TZM alloy used for welding is precisely processed by an automated lathe to meet the requirements of mass production, and to ensure the roughness of the welding surface and the uniform metallic luster of the surface, to ensure that the TZM welded parts and the solder form a good metallurgical bond, and there are no defects such as cracks or unwelded interfaces.

[0025] 2. The graphite used for welding is processed by lathe to form an annular "V"-shaped groove on the graphite welding surface. The solder melts and fills the "V"-shaped groove to produce a metallurgical reaction, forming a mutual bite state at the interface, thereby improving the interface strength and heat dissipation performance.

[0026] 3. The Zr-3 alloy solder used for welding is a conventional brand product with low cost and high melting point. It can form a good solid solution with Mo in TZM alloy and is suitable for mass production.

[0027] 4. Use high-temperature vacuum brazing technology. During the brazing process, maintain a high vacuum degree. The heating process is conducive to removing impurities such as gas adsorbed on the surface of the welding workpiece and inside the graphite, thereby improving the welding performance of the interface.

[0028] 5. The TZM / graphite joint interface obtained by welding in the present invention forms a good metallurgical bond, and the middle layer is Mo 2 It is composed of Zr, Mo-Zr solid solution and ZrC. Part of the solder penetrates into the graphite pores through capillary action to enhance the interface connection performance. There are no defects such as cracks or unwelded surfaces at the interface, and the interface shear strength is high.

[0029] 6. The TZM / graphite joint obtained by welding in the present invention is treated at high temperature (1500°C), and the joint does not remelt or undergo structural changes, and maintains good interface bonding strength. The interface shear strength remains almost unchanged from that before the high-temperature treatment, and the joint performance meets the requirements for use in high-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The figure is a schematic cross-sectional view showing the surface to be welded of graphite processed according to one embodiment of the present invention.

[0031] Figure 2 Schematic diagram showing the stacking of TZM alloy, Zr-3 and graphite according to one embodiment of the present invention.

[0032] Figure 3 This is a diagram showing the distribution of microstructure elements at the welding interface in the TZM / graphite welded part prepared according to Example 3 of the present invention.

[0033] Figure 4 The figure shows the interdiffusion line scan of the welding interface elements in the TZM / graphite welded part prepared according to Example 3 of the present invention.

[0034] Figure 5a To show the microstructure of the TZM / graphite welded parts prepared according to Example 3 of the present invention at the joint, and Figure 5bThe microstructure diagram of the joint of the TZM / graphite welded part prepared according to Example 3 of the present invention after being subjected to a high temperature test treatment at 1500°C is shown. DETAILED DESCRIPTION

[0035] The present invention will be described in detail below in conjunction with embodiments and drawings. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0036] The high-temperature vacuum brazing furnace used in the following examples is a vertical high-temperature vacuum furnace, and the maximum operating temperature can reach 2000°C. The shear strength test uses an in-situ tensile and compressive test system, and the shear rate is adjusted to 0.5 mm∙min -1 .

[0037] The TZM (Ti 0.4-0.55 wt%, Zr 0.06-0.12 wt%, C 0.01-0.04 wt%, the balance is Mo) alloy used in the following examples is in a rolled state with a diameter of 140 mm, and is from Xi'an Feilian New Materials Co., Ltd.; The graphite used is Sangao graphite, with a diameter of 140 mm and an ash content of <10 ppm, from Beijing Sanye Carbon Co., Ltd.; The solder used was a Zr-3 (Zr+Hf≥99.2 wt%, Hf≤4.5 wt%) foil with a diameter of 140 mm and a thickness of 0.3 mm, purchased from Zhongnuo New Materials (Beijing) Technology Co., Ltd.; TZM / graphite interface microstructure characterization: scanning electron microscopy; Shear strength measurement equipment: in-situ tension and compression testing system.

[0038] Implementation 1 TZM / graphite welds were prepared according to the following steps: Step 1: Take the TZM plate and turn it until the welding surface roughness Ra≤0.8, the welding surface metal luster is uniform and scratch-free, use 5% mass fraction dilute hydrochloric acid to ultrasonically clean the sample for 10 minutes, then use deionized cleaning for 10 minutes, and finally dehydrate with alcohol, then put it in a vacuum oven and evacuate it to 10Pa, maintain vacuum, heat it to 100℃, and dry it for 1h.

[0039] Step 2: Turn the graphite welding surface to form a ring-shaped "V"-shaped toothed groove surface on the welding surface (the cross-sectional schematic diagram of the processed graphite welding surface is shown in Figure 1 As shown), then use deionized water for ultrasonic cleaning for 10 minutes, then put it into a vacuum oven and evacuate it to 10Pa, maintain the vacuum, heat it to 100°C, and dry it for 8 hours.

[0040] Step 3: Wire-cut and grind the Zr-3 foil to remove the oxide layer on the surface, then use concentrated hydrochloric acid and deionized water in a ratio of 1:8 to clean and remove surface impurities, then use deionized water ultrasonic cleaning to remove the remaining acid, and blow dry for use as solder.

[0041] Step 4: Figure 2 As shown, using a fixed fixture, TZM alloy, Zr-3 solder and graphite are stacked in sequence to ensure that the weld is centered and there is good physical contact between the interfaces.

[0042] Step 5: Place the assembled TZM / Zr-3 / graphite assembly into a vacuum furnace and evacuate to 8*10 -4 Pa, start heating, heating rate is 15℃ / min, heating to 1200℃, then heating to 1560℃ at 8℃ / min, keeping warm for 10min, then cooling to room temperature at 10℃ / min, open the furnace and take out the TZM / graphite welded parts.

[0043] The interface joint shear strength of the TZM / graphite welded part prepared in this embodiment is 20 MPa.

[0044] Implementation 2 TZM / graphite welds were prepared according to the following steps: Step 1: Take the TZM plate and turn it until the welding surface roughness Ra≤0.8, the welding surface metal luster is uniform and scratch-free, use 5% mass fraction dilute hydrochloric acid to ultrasonically clean the sample for 10 minutes, then use deionized cleaning for 10 minutes, and finally dehydrate with alcohol, then put it in a vacuum oven and evacuate it to 10Pa, maintain vacuum, heat it to 100℃, and dry it for 1h.

[0045] Step 2: Turn the graphite welding surface to form an annular "V"-shaped toothed groove surface on the welding surface, then use deionized water for ultrasonic cleaning for 10 minutes, then put it into a vacuum oven and evacuate it to 10Pa, maintain the vacuum, heat it to 100℃, and dry it for 8 hours.

[0046] Step 3: Wire-cut and grind the Zr-3 foil to remove the oxide layer on the surface, then use concentrated hydrochloric acid and deionized water in a ratio of 1:8 to clean and remove surface impurities, then use deionized water ultrasonic cleaning to remove the remaining acid, and blow dry the solder to be used.

[0047] Step 4: Using a fixed fixture, stack the TZM alloy, Zr-3 solder, and graphite in sequence, ensuring that the weld is centered and that there is good physical contact between the interfaces.

[0048] Step 5: Place the assembled TZM / Zr-3 / graphite assembly into a vacuum furnace and evacuate to 8*10 -4 Pa, start heating, heating rate is 15℃ / min, heating to 1200℃, then heating to 1580℃ at 8℃ / min, keeping warm for 20min, then cooling to room temperature at 10℃ / min, open the furnace and take out the TZM / graphite welded parts.

[0049] The interface joint shear strength of the TZM / graphite welded part prepared in this example is 22 MPa.

[0050] Implementation 3 TZM / graphite welds were prepared according to the following steps: Step 1: Take the TZM plate and turn it until the welding surface roughness Ra≤0.8, the welding surface metal luster is uniform and scratch-free, use 5% mass fraction dilute hydrochloric acid to ultrasonically clean the sample for 10 minutes, then use deionized cleaning for 10 minutes, and finally dehydrate with alcohol, then put it in a vacuum oven and evacuate it to 10Pa, maintain vacuum, heat it to 100℃, and dry it for 1h.

[0051] Step 2: Turn the graphite welding surface to form an annular "V"-shaped toothed groove surface on the welding surface, then use deionized water for ultrasonic cleaning for 10 minutes, then put it into a vacuum oven and evacuate it to 10Pa, maintain the vacuum, heat it to 100℃, and dry it for 8 hours.

[0052] Step 3: Wire-cut and grind the Zr-3 foil to remove the oxide layer on the surface, then use concentrated hydrochloric acid and deionized water in a ratio of 1:8 to clean and remove surface impurities, then use deionized water ultrasonic cleaning to remove the remaining acid, and blow dry for use as solder.

[0053] Step 4: Using a fixed fixture, stack the TZM alloy, Zr-3 solder, and graphite in sequence, ensuring that the weld is centered and that there is good physical contact between the interfaces.

[0054] Step 5: Place the assembled TZM / Zr-3 / graphite assembly into a vacuum furnace and evacuate to 8*10 -4 Pa, start heating, heating rate is 15℃ / min, heating to 1200℃, then heating to 1600℃ at 8℃ / min, keeping warm for 20min, then cooling to room temperature at 10℃ / min, open the furnace and take out the TZM / graphite welded parts.

[0055] The TZM / graphite welded parts prepared in this embodiment were cut and subjected to joint strength test and interface structure characterization, wherein the interface joint shear strength was 32 MPa.

[0056] Figure 3 The figure shows the distribution of microstructure elements at the welding interface of the TZM / graphite welded parts prepared above. It can be seen from the figure that the TZM alloy and graphite have achieved good metallurgical bonding through the solder, and there are no defects such as cracks, holes or unwelded surfaces at the interface. The "V"-shaped toothed grooves of the graphite are filled with solder, and the melted solder penetrates into the graphite through capillary action to form an island structure, which is beneficial to improving the interface strength.

[0057] Figure 4 The figure shows the interdiffusion line scan of the elements at the welding interface in the TZM / graphite welded parts prepared as described above. From the figure, we can see the distribution of elements extending from graphite to the TZM alloy side. In the graphite matrix, there are ZrC and Zr-Mo solid solutions. A ZrC layer is formed at the interface between graphite and solder. The middle part of the solder is mainly Mo. 2 Zr exists in the form of Zr-Mo solid solution, and Mo is formed at the interface between TZM alloy and solder. 2 The Zr phase forms a metallurgical bond with the TZM alloy, which proves that during the welding process, Mo atoms fully diffuse to the solder side, the solder melts and fills the interface pores, and the corresponding alloy phase precipitates during the cooling and solidification process to form a good metallurgical bonding interface.

[0058] High temperature test: The prepared TZM / graphite welded parts were placed in a vacuum medium frequency furnace, heated to 1500°C and then stopped heating. After cooling to room temperature, they were taken out for interface structure and strength testing.

[0059] After being treated at 1500℃, the TZM / graphite interface did not remelt or produce cracks, and the interface strength still reached 30MPa after testing. Through further microstructural analysis, it can be seen that the interface structure is mainly composed of Mo 2 It is composed of Zr, Zr-Mo solid solution and zirconium carbide, and no organizational changes occur.

[0060] Figure 5a To show the microstructure of the TZM and graphite joint of the prepared TZM / graphite welded parts, Figure 5a As can be seen in the figure, the Mo in the solder layer 2 Zr is mainly in the form of long strips, which is the organizational structure formed when the solder melts and slowly cools and the components solidify and precipitate. There are no cracks, holes or unwelded areas at the interface.

[0061] Figure 5b To show the microstructure of the TZM and graphite joints of the prepared TZM / graphite welded parts after high temperature test at 1500℃, Figure 5b It can be seen that after high temperature treatment, the Mo in the solder layer 2 Zr is still in the form of long strips, and Mo at the interface of the TZM alloy2 Zr still has a tooth-like structure, and there are no defects such as cracks or holes on the interface. The interface can maintain good organizational structure and mechanical strength.

[0062] Compared with TZM alloy / graphite welded parts connected by using pure zirconium layers (see CN114453693A), the TZM alloy / graphite welded parts obtained by the method of the present invention have significantly improved interface joint shear strength.

[0063] It can be seen that the TZM / graphite welded parts obtained by the method of the present invention can meet the use requirements in high temperature environments.

Claims

1. A vacuum brazing method for connecting TZM alloy and graphite, comprising the following steps: Step 1: Turning or grinding the TZM alloy sheet, and cleaning and drying it; Step 2: Turn the graphite welding surface to form a toothed welding interface, and then clean and dry it; Step 3: Cut the Zr-3 foil as solder, grind it, clean it with acid, and dry it for later use; Step 4: stacking the TZM alloy plate obtained in step 1, the Zr-3 foil obtained in step 3, and the graphite obtained in step 2 in sequence to ensure good physical contact between the interfaces; Step 5: Place the assembled TZM / Zr-3 / graphite assembly into a vacuum furnace, then start heating after vacuuming, with a heating rate of 15°C / min to 1200°C, and then heat to 1550~1630°C at 8°C / min, and keep it warm for 5~20 minutes for vacuum brazing, then gradually cool down or cool to room temperature with the furnace, open the furnace and take out the TZM / Zr-3 / graphite welded parts.

2. The vacuum brazing method for connecting TZM alloy and graphite according to claim 1, wherein: The surface roughness Ra of the TZM plate obtained in step 1 is less than 0.

8. And / or, the diameter of the TZM plate obtained in step 1 is 100-220 mm.

3. The vacuum brazing method for connecting TZM alloy and graphite according to claim 1 or 2, wherein: The cleaning in step 1 is to use 3% to 15% mass fraction of dilute hydrochloric acid for ultrasonic cleaning for 10 minutes, then use deionized water for ultrasonic cleaning for 10 minutes, and then use alcohol for cleaning and dehydration.

4. The vacuum brazing method for connecting TZM alloy and graphite according to any one of claims 1 to 3, wherein: The toothed interface to be welded described in step 2 refers to an annular "V"-shaped groove formed on the interface to be welded; And / or, the diameter of the graphite obtained in step 2 is 100~220mm.

5. The vacuum brazing method for connecting TZM alloy and graphite according to claim 4, wherein: The depth of the annular "V"-shaped groove is 0.2~0.8mm, and the width of the top of the groove is 0.3~1.0mm.

6. The vacuum brazing method for connecting TZM alloy and graphite according to any one of claims 1 to 5, wherein: The thickness of the Zr-3 solder obtained in step 3 is 0.1 to 0.8 mm, preferably 0.2 to 0.4 mm; And / or, the diameter of the Zr-3 solder obtained in step 3 is 100~220mm.

7. The vacuum brazing method for connecting TZM alloy and graphite according to any one of claims 1 to 6, wherein: The wire cutting and grinding process in step 3 refers to cutting the solder into corresponding shapes, and then grinding with 400-grit and 2000-grit sandpaper to remove the surface oxide layer; And / or, the pickling described in step 3 refers to using concentrated hydrochloric acid and deionized water in a weight ratio of 1:5-10, then immersing Zr-3 in the acid solution to clean surface impurities, then using deionized water ultrasonic cleaning to remove the acid solution, and finally blowing it dry for standby use.

8. The vacuum brazing method for connecting TZM alloy and graphite according to any one of claims 1 to 7, wherein: The vacuum at the start of heating in step 5 is 7*10 -4 Up to 9*10 -4 Pa.

9. The vacuum brazing method for connecting TZM alloy and graphite according to any one of claims 1 to 8, wherein: The gradient cooling described in step 5 means cooling to 1000° C. at a cooling rate of 10° C. / min after the brazing is completed, and then cooling to room temperature along with the furnace.

10. The TZM alloy / graphite welded part prepared by the vacuum brazing method for connecting TZM alloy and graphite according to any one of claims 1 to 9, wherein the interface joint shear strength of the TZM alloy / graphite welded part is preferably above 18 MPa, more preferably above 19 MPa, and even more preferably above 22 MPa.

Citation Information

Patent Citations

  • Vacuum hot-pressing diffusion welding method for molybdenum and graphite

    CN105397264A

  • SPS non-pressure brazing method for TZM alloy and graphite

    CN113770467A

  • Contact reaction brazing process for connecting TZM alloy and graphite through pure zirconium layer

    CN114453693A

  • Eutectic reaction brazing process of graphite and TZM alloy

    CN114932283A